Effect of experimental feed additives on aflatoxin in milk of dairy cows fed aflatoxin‐contaminated diets. Issue 4 (7th June 2012) - Kissell, L.; Davidson, S.; Hopkins, B. A.; Smith, G. W.; Whitlow, L. W.
Summary Three studies were conducted to determine the potential of experimental feed additives (EFAs), clays or non‐digestible yeast oligosaccharides, to reduce milk aflatoxin (AFM1) concentrations in lactating Holstein cows consuming aflatoxin‐contaminated diets. All studies included a pre‐treatment period and a 2‐week experimental period in a randomized block design. During the pre‐treatment period, cows received a total mixed ration (TMR) with no aflatoxin contamination. During both experimental weeks, all cows were fed a TMR containing aflatoxin‐contaminated corn. During experimental week 1, cows received no EFA's in the TMR, but EFA's were included in the TMR for the second experimental week. In studies 1 and 2, the experimental period consisted of 2 weeks each lasting 7 days with 12 cows per treatment. Aflatoxin M1 concentrations were analysed by HPLC for milk samples collected on days 5–7 and days 11–14. In various experiments, treatments included control (no EFA), 100 g/cow daily of experimental Lallemand® product, 10 g/cow daily of MTB‐100®‐2004, (Alltech, Inc.), 10 g/cow daily of MTB‐100®‐2006, (Alltech, Inc.), 10 g/cow daily of experimental Alltech® product (Alltech, Inc.) and 227 g/cow daily of Astra‐Ben 20® (AB‐20®; Prince Agri Products, Inc.). In study 3, the experimental period of 2 weeks each lasting 8 days and milk samples were collected from day 4 to 8 and day 11 to 16. Milk samples from study 3 were analysed for AFM1 concentrations by ELISA. For all experiments, changes in AFM1 concentrations because of the addition of EFA's were calculated. Four of the five EFAs tested in this study had no significant effect on AFM1 concentrations. However, the addition of AB‐20® resulted in a significant decrease in AFM1 concentrations (60.4%). In summary, the addition of AB‐20® to the diet of cattle appears to be effective for significantly reducing AFM1 concentrations in the milk of cows fed an aflatoxin‐contaminated diet.